Effect of LHCGR Gene Polymorphism (rs2293275) on LH Supplementation Protocol Outcomes in Second IVF Cycles: A Retrospective Study - GA, Ramaraju; Cheemakurthi, Ravikrishna; Kalagara, Madan; Prathigudupu, Kavitha; Balabomma, Kavitha Lakshmi; Mahapatro, Pranati; Thota, Sivanarayana; Kommaraju, Aruna Lakshmi; Muvvala, Sanni Prasada Rao (Frontiers in Endocrinology, 2021)
Abstract Infertility is a major concern for couples wanting to have progeny. Despite recent advances in the field of IVF, success rates still need improvement. Understanding the patient's variability and addressing it with personalized interventions may improve the success rate of fertilization and live births. This study examined the impact of a personalized pharmacogenomic approach on LH supplementation on the pregnancy and live birth rate outcomes in comparison with the traditional approaches. 193 patients undergoing a second IVF cycle in Krishna IVF Clinic received LH supplementation either as per the conventional methods or based on N312S (rs2293275) LHCGR gene polymorphism. Results showed a significant increase in pregnancy rate (P-value: 0.049) and a trend showing improvement in live birth rates (P-value: 0.082). When r-hLH supplementation protocol was decided as per the genotypes A/A, A/G, and G/G of the N312S variant in the respective patients. This stimulation regimen helped in providing optimum levels of r-hLH supplementation to patients with impaired hormone-receptor interacting activity, to achieve higher success in pregnancy and live birth rates.